Performance Analysis of a Priority Based Buffer-Aided Relaying - SP , Swain; PK , Swain (International Journal of Computer Sciences and Engineering, 2019)
Wireless Body Area Network (WBAN) is a collection of low power sensing devices which are either implant inside human body or on-body devices. This network helps to transmit vital parameters of body over wireless network to the remote server. Among different categories of body parameters some of are supposed to be vital and required to transmit faster than others, so that necessary actions can be made in time. In this paper we have studied various literatures on conventional WBAN, IoT based WBAN, Buffer-Aided Relaying Frame work etc. and proposed a model to handle priority based on-body sensor data(e.g. Heart Rate Data, Blood Sugar Data and EEG data) along with relaying node with buffer. The priority level is analyzed by a priority analyzer node. This model is simulated using Java Modelling Tool (JMT) and various performance matrices like Response Time, Throughput, Queue Time, Utilization, etc. are analyzed in terms of simulation graphs. Our model out performs for prioritized data than the non-prioritized data as represented in the result section.